Mothering in the Context of Mental Disorder: Effect of Caregiving Load on Maternal Health in a Predominantly Hispanic Sample. (September 2021) - Matsuda, Yui; McCabe, Brian E.; Behar-Zusman, Victoria
Background: Mothering in the context of mental disorders presents with multiple challenges. However, this phenomenon is poorly understood: It is not known how child caregiving affects the health of their mothers. Aims: The purpose of this study was to examine associations between child caregiving load and health indicators in mothers receiving outpatient behavioral health services for mental or substance use disorders. Method: A total of 172 mothers (80% Hispanic/Latina) completed surveys on their mental and physical health, and children's behaviors and medical problems. Child caregiving load consisted of number of children living with the mother, and presence of children's internalizing, externalizing, or medical problems. Results: Child caregiving load had significantly positive associations with mother's psychological distress, fatigue, pain, and body mass index. Child internalizing and medical problems were associated with mothers' poor health status. Conclusions: Hispanics/Latinos experience health disparities, and Hispanic/Latina mothers who are already at risk due to their mental disorders experience an additional health burden associated with caring for children with emotional or health problems. Psychiatric and mental health nurse practitioners should assess child caregiving impact on mothers with mental disorders and seek to mitigate their caregiving burden and maintain their health. Further research is needed to clarify child characteristics and the mechanisms associated with maternal caregiver burden, suboptimal self-care, and adverse health outcomes. Structural Ecosystems Therapy for women in Recovery (SET-R) study/Healthy Home; Clinical Trial ID NCT02702193